The impact of cannabis use on short-term educational outcomes - Lionel Perini; Joachim Marti (University of Neuchâtel, Institute of Economic Research (IRENE), 2013)
In this paper we use longitudinal data on Swiss adolescents to nvestigate the impact of cannabis use on short-term educational performance. We focus our analysis on high school students and analyze various outcomes, including absenteeism, grades, and motivation. We exploit the panel nature of the data and control for a rich set of individual and family characteristics measured at the end of compulsory school. Results from both fixed effects regressions and propensity score matching indicate that high school students who smoke cannabis skip on additional half day of school per month and are 15-20% more likely to obtain poor grades. In addition, our empirical approaches highlight the importance of taking unobserved heterogeneity into account when assessing the impact of substance use on education.
Keywords: I12; I18; I21; C23; 330; cannabis; education; adolescents; human capital; propensity score matching